Numerical Study of Flow and Heat Transfer Characteristics on Flat Fin with Staggered Tube Arrangement in Transitional Turbulent Flow - Mahadika Favian Alfandaviska; Prabowo Prabowo (JMES: The International Journal of Mechanical Engineering and Sciences, 2020)
Three-dimensional computational fluid dynamic simulations were conducted for flow and heat transfer characteristics around flat fin with staggered tube arrangement to fulfill the cooling performance of the tube fin heat exchanger. Fins are generally used to increase the heat transfer area, so the fin material has a high impact on the heat transfer rate. The material wall fin and tube were changed in three steps: aluminum, steel, copper with two different velocities of 8 and 15 m/s flowing between fins. The geometry of the flat fin and tube used staggered tube arrangement using transversal spacing, ST, of 11.8 mm, longitudinal spacing, SL, of 22.2 mm, and flow depth 66.6 mm. GAMBIT 2.6 software was used to meshing the geometry, and FLUENT 18.0 was implemented to simulate flow and heat transfer. The results show that the fin with copper material has a more uniform temperature distribution along the fin than the other materials. This indicates that the copper material has a higher heat transfer rate compared to aluminum and steel. Furthermore, increasing velocity will make the separation point formation farther behind the tube and decrease the recirculation zone. Moreover, 8 m/s has a lower outlet temperature than 15 m/s. As a result, 8 m/s and copper material have the highest effectiveness of 16.47 and efficiency of 88.35 %. The use of copper and aluminum as fin material will also have the relatively same performance in the heat exchanger.